High‐gain observers for leak location in subterranean pipelines of liquefied petroleum gas. (18th September 2012) - Torres, L.; Verde, C.; Besançon, G.; González, O.; Khalil, Hassan K.; Praly, Laurent
SUMMARY This paper describes a scheme based on high‐gain observers to detect and locate leaks in subterranean pipelines of liquefied petroleum gas (LPG). In fact, sub‐observers connected in cascade are used to generate residuals that allow to detect when a leak occurs and, above all, to isolate the region of the pipeline where the leak is located. Once the region is identified, a dedicated observer is employed to more precisely estimate the leak position as well as its coefficient. The approach is validated with data from a real industrial LPG pipeline. Copyright © 2012 John Wiley & Sons, Ltd.